Math, asked by reddykmahita, 2 months ago

2 – [3 – {6 – (5 – 4 – 3)}]​

Answers

Answered by RMRM3
1

Answer:

7

Step-by-step explanation:

# 2 - [ 3 - { 6 - ( 5 - 4 - 3 ) }

solution_

= 2 - [ 3 - { 6 -( - 2 ) } ]

= 2 - [ 3 - 8 ]

= 2 - ( - 5 )

= 7

: Hope it will help you.

Answered by havellshavells522
1

Step-by-step explanation:

2 – [3 – {6 – (5 – 4 – 3)}]

=2 – [3 – {6 – (5 – 7)}]

=2 – [3 – {6 – (-2)}]

=2 – [3 – {6+2)]

=2 – [3 – {8)]

=2 – [3 – 8]

=2 - (-5)

=2+5

=7

this is the answer

give me more likes, thanks

Similar questions